1994
DOI: 10.1111/j.1365-2044.1994.tb03578.x
|View full text |Cite
|
Sign up to set email alerts
|

Single oral dose ondansetron in the prevention of postoperative nausea and emesis

Abstract: SummaryIn two placebo-controlled, double-blind, multicentre 0.007; nausea p Key wordsPharmacology; ondansetron, oral formulation. Complications; nausea and vomiting. Receptors; 5-HT3. Vomiting; antiemetics, prophylaxis.Postoperative nausea and vomiting (PONV) are among the most common complications that occur after surgery performed under general anaesthesia, with female patients being particularly susceptible [ 11. Other factors, including a previous history of PONV and the site of surgery, are thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
5

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 7 publications
1
20
0
5
Order By: Relevance
“…Dizziness has also been reported in phase I (13%) and phase II (5%) dolasetron studies as well as following a single oral dose of ondansetron for the prevention of emetic symptoms (3.4%). 19 Droperidol, ondansetron, granisetron, transdermal scopolamine, and most recently perphenazine 23 are effective in preventing PONV. In that recent study, droperidol, ondansetron, and perphenazine were equally effective in reducing PONV for the first four hours after surgery but the authors concluded that perphenazine was the drug of choice because of its low cost and low incidence of side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dizziness has also been reported in phase I (13%) and phase II (5%) dolasetron studies as well as following a single oral dose of ondansetron for the prevention of emetic symptoms (3.4%). 19 Droperidol, ondansetron, granisetron, transdermal scopolamine, and most recently perphenazine 23 are effective in preventing PONV. In that recent study, droperidol, ondansetron, and perphenazine were equally effective in reducing PONV for the first four hours after surgery but the authors concluded that perphenazine was the drug of choice because of its low cost and low incidence of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Complete responses for the prevention of PONV were 54% in a European study is and 52% in a U.S. study. 19 All 5-HT 3 receptor antagonists prolong intracardiac conduction. Batanopride (BMY-25801), a 5-HT 3 receptor antagonist investigated as an antiemetic in patients receiving cancer chemotherapy, produced dose-dependent prolongation of QRS and Q-Tc at doses required for antiemetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Its use in the prevention and treatment of PONV is relatively new and optimal administration times have yet to be determined (Dupeyron et al, 1993;Rust & Cohen, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…São, todavia, relativamente poucos os estudos que tratam da eficá-cia da ondansetrona oral na prevenção de NVPO 6,7,[112][113][114][115][116][117] . No presente estudo, buscou-se confirmar a eficácia da administração oral pré-operatória deste fármaco em intervenções com duração não superior a 3 horas.…”
Section: Discussionunclassified
“…Assim, a disponibilidade de 16 mg deste fármaco após a administração oral equivale a 8 mg em injeção intravenosa 108 . Em razão do exposto, nesta investigação optou-se por veicular a ondansetrona em comprimidos de dissolução instantânea e definiu-se 16 mg de ondansetrona, dose que se mostrou efetiva no presente estudo e em outros encontrados na literatura 112,114,116 .…”
Section: Discussionunclassified